Helpful Governments - Amin, Mohammad (World Bank, Washington, DC, 2012)
This paper provides an alternative way of testing the theory of legal origins, one based on a firm's perception of how helpful the government is for doing business. The author argues that an approach based on firm perceptions offers a number of advantages over existing studies. Specifically, the analysis demonstrates that heavier regulation in civil law compared with common law countries is not viewed by businesses as an efficient and socially desirable response to disorder. Further, the findings show a strong effect of legal tradition on government helpfulness even after controlling for various institutional measures known to be correlated with the legal tradition of countries. This suggests that there is more to legal tradition than what existing studies have unearthed.